Comparison of Different Types of Corneal Foreign Bodies Using Anterior Segment Optical Coherence Tomography: A Prospective Observational Study - Tao Wang; Lei Zhong; Shiyi Yin; Tiancheng Bao; Jiezheng Yang; Ting Wang; Shiqi Ling (Journal of Ophthalmology)
Purpose. The present study highlighted the value of anterior segment optical coherence tomography (AS-OCT) for different types of corneal foreign bodies in humans. Methods. This study was a prospective observational study. The patients included were divided into two groups. If the patients were directly diagnosed based on eye injury history and slit-lamp examination, then they were assigned to Group A. Otherwise, the patients were assigned to Group B. We compared and described the characteristics of the corneal foreign body in both groups using AS-OCT. Results. From October 2017 to January 2020, 36 eyes of 36 patients (9 females and 27 males) with a mean age of 37.8 ± 11.7 years were included in the study. Patients in Group A were the majority and accounted for 72.2% (26/36). High signals on AS-OCT images were the main constituent and accounted for 92.3% (24/26) in Group A and 70.0% (7/10) in Group B. Most of the patients in Group A, 96.2% (25/26), had clear boundaries. A blurred boundary was observed in 70.0% (7/10) of the patients in Group B. The foreign bodies on AS-OCT images had key characteristics of a high signal followed by a central zone shadowing effect and a low signal followed by a marginal zone shadowing effect. Further, all of the lesions could be directly located in Group B, and 92.3% (24/26) of the patients in Group A did not have directly located lesions. Six representative cases are described in detail. Conclusions. AS-OCT is a valuable tool in the diagnosis and management of corneal foreign bodies, especially for unusual corneal foreign body.